Clinical and cranial MRI features of female patients with ornithine transcarbamylase deficiency: Two case reports. Issue 33 (August 2019) - Yu, Dan; Lu, Guoyan; Mowshica, Rajah; Cheng, Yan; Zhao, Fumin
Abstract: Introduction: Ornithine transcarbamylase deficiency (OTCD) is a common metabolic disease of urea circulation disorder. We reported the clinical, brain imaging and genetic characteristics of 2 cases with OTCD. The patients' clinical features, novel gene mutations, cranial MR specific imaging changes and blood tandem mass spectrometry, and urine gas chromatography-mass spectrometry were, retrospectively, analyzed. Patient concerns: Patient 1 was a 1.6-year-old female. She was admitted to the hospital with 2-months history of general irritability and disturbance of consciousness for a day. Patient 2 was a 3.7-year-old female. She was admitted to the hospital due to decline of language ability and irritability for 5 days. Blood tandem mass spectrometry and urine gas chromatography-mass spectrometry showed uracil and orotate increased significantly in urine while amino acids in the urea cycle ring were in the normal range. The features of brain MRI are consistent with those of urea circulatory disorders. Gene detection showed 1 novel mutation in the OTC gene (c.658C>T) in patient 1 and, 1 novel mutation (c.298+2T>G) in the OTC gene in patient 2. Diagnosis: Combined with metabolic screening and gene detection, both patients were diagnosed with OTCD. Interventions: The patients' condition improved after following a low protein diet and receiving treatments for decreasing blood ammonia, energy supplement, correcting acid-base imbalance, and other symptomatic treatments. Outcomes: After prompt symptomatic treatment, the consciousness and cognition of the children improved. Besides, liver function also improved significantly. Conclusions: For patients with neurological symptoms and unexplained increase in transaminase and ammonia, OTCD should be considered as a possible diagnosis. Brain MRI can help the diagnosis of genetic metabolic encephalopathy and reflect the level of brain injury. Metabolic screening and genetic detection are helpful to make a confirmed diagnosis.